PERFORMANCE OF BIOFILTER AND WATER HYACINTH PHYTOREMEDIATION FOR LEACHATE TREATMENT - Sugito Sugito; Risa Aulia Divanda Rahmadani; Sitti Adiyaksa Fazrian (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2026)
Leachate is a significant pollutant source with the potential to cause environmental damage, particularly through soil infiltration that degrades groundwater quality. This study evaluates a treatment method combining aerobic biofilters and phytoremediation to reduce pollutant levels in leachate from the Ngipik Landfill, Gresik Regency. The treatment utilized biofilters with varying media—bioballs, plastic straws, and oyster shells—integrated with phytoremediation using water hyacinth (Eichhornia crassipes) in a continuous downflow system with a 24-hour retention time. Sampling was conducted from day 0 to day 3. Analysis followed standard procedures: SNI 6989.72:2009 for BOD, SM APHA 24th Ed. 2540 D (2023) for TSS, and SM APHA 24th Ed. 3112 B (2023) for Hg. The results indicate that this combined method effectively reduces pollutants, achieving maximum reduction efficiencies of 83% for BOD (bioball media), 94% for TSS (plastic straw media), and 93% for Hg across all media types.